Benedict's Rule : A Translation and Commentary - Kardong, Terrence (Book collections on Project MUSE., 1996)
Through the ages many commentaries have been written on the Rule of Benedict. Usually these books were the practical reflections of a busy abbot, and they tended to concentrate on a few favorite chapters and verses of the Rule. Now, however, scholars are applying literary and historical criticism to studies of the Rule with impressive results. For the past fifteen years, Fr. Terrence Kardong, O.S.B., has written monographs on important parts of the Rule. Now in Benedict's Rule he has completed a line-by-line exegesis of the entire Rule - the first such in the English language. This commentary is based on a new translation, and it is accompanied by essays on Benedict's spiritual doctrine. The Latin texts of the Rule, as published in RB 1980 (The Liturgical Press, 1981), are included. The book also has a massive bibliography of current scholarship on the Rule.